Finance fragmented? Frankfurt and Paris as European financial centres after Brexit. Issue 10 (3rd October 2019) - Lavery, Scott; McDaniel, Sean; Schmid, Davide
ABSTRACT: Brexit creates an opportunity for alternative European financial centres. However, no comprehensive empirical analysis of the strategic positioning of actors within these financial centres has been conducted. In this article we outline findings from an extensive research project which we conducted in Frankfurt and Paris, two of the main 'rivals' to the City of London, in the aftermath of Brexit. We outline the core findings from this project and argue that the emerging competition between Frankfurt and Paris is shaped through four related axes: diversity, path dependency, territory and regulatory stability. Our analysis has implications for two bodies of literature within EU studies. First, inter-governmentalist and supra-nationalist approaches would benefit from interrogating more closely the contested sub-national politics of financial centres. Second, our analysis adds to a growing body of literature on European disintegration by interrogating the interaction of fragmentary and integrative dynamics in the sphere of European finance.